Acrylamide Content in Food Commodities Consumed in North Macedonia and Its Risk Assessment in the Population - Dimitrieska-Stojkovikj, E.; Angeleska, A.; Stojanovska-Dimzoska, B.; Hajrilai-Musliu, Z.; Koceva, D.; Uzunov, R.; Ilievska, G.; Stojković, G.; Jankuloski, D. (Knowledge E, 2019)
Background: Acrylamide (AA) is an important food contaminant resulted from Maillard reaction during thermal processing of carbohydrate rich food commodities. The present paper reports the data for the AA content in some types of thermally processed starch rich food, and assessment of dietary exposure for the population in North Macedonia. Methods: The AA level was determined employing modified and validated ultra high performance liquid chromatography with tandem quadrupole detector. A total of 160 samples divided in seven most frequently consumed commodity groups were collected for determination of their AA content. Finally, chronic exposure of AA in the population was estimated. Statistical analysis was performed applying OriginPro 8 SR4 v8.0951 software package Results: The average AA levels varied from 126.9±122.4 μg/kg for bread samples to 494.5±127.1 μg/kg for French fries samples. The dietary exposure of the population from North Macedonia for the tested food commodities was estimated at 0.643±0.171 μgAA/kgbw/day. The main contributor to the total AA intake was bread, with estimated value at 0.394±0.150 μgAA/kgbw/day. The margin of exposure values were 528 and 264, respectively for neurotoxicity and non-plastic effect calculated on average intake. Conclusion: The risk assessment analysis revealed increased concern for human health regarding the neoplastic effects, especially for infants, toddlers, and adolescents. This is the first study related to AA presence in different food commodities in North Macedonia, and implies that monitoring programs and mitigation strategies must be implemented.